2016
DOI: 10.1111/jopr.12552
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Pressure Redistribution with Single Implant Restorations

Abstract: Single posterior implant-supported restorations significantly increased the percentage (%) of total occlusal pressure in the containing sextant and decreased percentage of total occlusal pressure in the contralateral sextant. When analyzing restorations by exact position, more posterior implant restorations decreased the occlusal pressure applied in anterior dentitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
(18 reference statements)
2
19
0
2
Order By: Relevance
“…This finding is consistent with the result of Roque et al, 26 who demonstrated that placement of single posterior implant-supported restorations opposed by natural dentition decreased the percentage of total occlusal pressure in the contralateral arch. This indicates the unity of the whole dental arch to distribute each force, as well as the influence of each tooth on the intensity of the applied force on the other teeth in the same jaw.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the result of Roque et al, 26 who demonstrated that placement of single posterior implant-supported restorations opposed by natural dentition decreased the percentage of total occlusal pressure in the contralateral arch. This indicates the unity of the whole dental arch to distribute each force, as well as the influence of each tooth on the intensity of the applied force on the other teeth in the same jaw.…”
Section: Discussionsupporting
confidence: 92%
“…The comparison of stresses formed at the anterior and posterior regions of bones and implants showed generally higher stresses in the posterior regions in all models. Perhaps the main reason for this finding is the location of posterior implants in the center of the chewing area . This should be considered when designing implant‐supported fixed prostheses similar to the All‐on‐Four concept.…”
Section: Discussionmentioning
confidence: 99%
“…Forces were defined on contacts formed in maximum intercuspation, lateral, and protrusive movement postion in the canine‐guided occlusion, group function occlusion, BBO, lingualized occlusion, and monoplane occlusion (Fig ). While defining the forces, the mean values for maximal occlusal loads during chewing were used for fully implant‐supported prostheses The occlusal loads were the same in all occlusion types in the case of maximum intercuspation (450 N); however, it has been shown that these occlusal loads change on lateral and protrusive movements between the occlusion types . The applied occlusal loads were 93 N for canine‐guided occlusion and 200 N for group function occlusion on lateral movement, 94 N for canine‐guided and group‐function occlusion on protrusive movement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations